The Value of Looking into the Future: Top Managers' Long Term Orientation and ESG Engagement - Huang, Yufei (My University, 2026)
Although prior research has explored how managers’ intuitive and affective processing mechanisms shape corporate ethical behaviors, limited attention has been dedicated to top managers’ temporal cognitive orientation—a relatively stable tendency to perceive time. Drawing on upper echelons theory and the attention-based view, we theorize that long-term orientation expands managerial attention to encompass the future consequences of current decisions, thereby affecting environmental, social, and governance (ESG) engagement. This study first uses text analysis and machine learning methods to construct top managers’ long-term orientation index and then empirically tests three hypotheses employing the panel data of Chinese A-share listed companies from 2010 to 2023. The results of a high-dimensional fixed effect model indicate that long-term- oriented top managers engage more substantively with ESG initiatives. The conclusion remains robust after various checks. We also find that regulatory pressure and shareholder value strengthen the positive impact of long-term orientation on ESG engagement. This study contributes to business ethics by demonstrating that long-term orientation serves as a cognitive foundation that enables ESG engagement by fostering a thicker conception of corporate responsibility.
PUBLISHED
Keywords: Long-term orientation; ESG engagement; Upper echelons theory; Attention-based view; Machine learning